Stroke-Induced Modulation of Myeloid-Derived Suppressor Cells (MDSCs) and IL-10-Producing Regulatory Monocytes - Achmus, Lennart; Ruhnau, Johanna; Grothe, Sascha; von Sarnowski, Bettina; Bröker, Barbara M.; Dressel, Alexander; Schulze, Juliane; Vogelgesang, Antje (Frontiers in Neurology, 2020)
Background: Stroke patients are at risk of acquiring secondary infections due to stroke-induced immune suppression (SIIS). Immunosuppressive cells comprise myeloid-derived suppressor cells (MDSCs) and immunosuppressive interleukin 10 (IL-10)-producing monocytes. MDSCs represent a small but heterogeneous population of monocytic, polymorphonuclear (or granulocytic), and early progenitor cells (“early” MDSC), which can expand extensively in pathophysiological conditions. MDSCs have been shown to exert strong immune-suppressive effects. The role of IL-10-producing immunosuppressive monocytes after stroke has not been investigated, but monocytes are impaired in oxidative burst and downregulate human leukocyte antigen—DR isotype (HLA-DR) on the cell surface. Objectives: The objective of this work was to investigate the regulation and function of MDSCs as well as the immunosuppressive IL-10-producing monocytes in experimental and human stroke. Methods: This longitudinal, monocentric, non-interventional prospective explorative study used multicolor flow cytometry to identify MDSC subpopulations and IL-10 expression in monocytes in the peripheral blood of 19 healthy controls and 27 patients on days 1, 3, and 5 post-stroke. Quantification of intracellular STAT3p and Arginase-1 by geometric mean fluorescence intensity was used to assess the functionality of MDSCs. In experimental stroke induced by electrocoagulation in middle-aged mice, monocytic (CD11b+Ly6G−Ly6Chigh) and polymorphonuclear (CD11b+Ly6G+Ly6Clow) MDSCs in the spleen were analyzed by flow cytometry. Results: Compared to the controls, stroke patients showed a relative increase in monocytic MDSCs (percentage of CD11b+ cells) in whole blood without evidence for an altered function. The other MDSC subgroups did not differ from the control. Also, in experimental stroke, monocytic, and in addition, polymorphonuclear MDSCs were increased. The numbers of IL-10-positive monocytes did not differ between the patients and controls. However, we provide a new insight into monocytic function post-stroke since we can report that a differential regulation of HLA-DR and PD-L1 was found depending on the IL-10 production of monocytes. IL-10-positive monocytes are more activated post-stroke, as indicated by their increased HLA-DR expression. Conclusions: MDSC and IL-10+ monocytes can induce immunosuppression within days after stroke.